Virtual Technologies in a Demand Virtualization Environment : Expanding the Potential of Fashion Brands - Karpushkin, Gleb (Indian Journal of Marketing, 2025)
Purpose : This research aimed to evaluate the potential impact of implementing augmented reality (AR) on online sales by measuring customersâ€™ perceptions of augmented and physical reality in terms of size, fit, and aesthetic appearance parameters. Methodology : The experimental sample comprised of 91 participants. Data collection involved a one-way analysis of variance with repeated measures. The within-subjects research method (repeated measures) was employed, wherein each participant tested all scenarios (in conditions of AR fitting and traditional physical fitting of clothing). The assessment of the variablesâ€™ impact on shaping purchase intention was conducted using a multivariate analysis of variance. Findings : It was demonstrated that AR ensures consistency in the overall impression of the product for the consumer; however, the correspondence between AR and real fitting has been only partially confirmed. The significance of self-perception during virtual try-ons in shaping purchase intention was underscored. Practical Implications : The practical implications entailed recommending the implementation of AR solutions in online sales to enhance customer loyalty, reduce clothing returns, and increase loyalty to online purchases. Originality : The study contributed to the further development of the â€œstimulus-organism-responseâ€ model for the conditions that AR shapes in online sales and provided new experimental data that aided fashion brands in leveraging the advantages of AR.